Ancient China a history - Major, John S.; Cook, Constance A. (Routledge/Taylor & Francis Group, 2017)
"Ancient China: A History surveys the East Asian Heartland Region -- the geographical area that eventually became known as China -- from the Neolithic period through the Bronze Age, to the early imperial era of Qin and Han, up to the threshold of the medieval period in the third century CE. For most of that long span of time there was no such place as "China"; the vast and varied territory of the Heartland Region was home to many diverse cultures that only slowly coalesced, culturally, linguistically, and politically, to form the first recognizably Chinese empires. The field of Early China Studies is being revolutionized in our time by a wealth of archaeologically recovered texts and artifacts. Major and Cook draw on this exciting new evidence and a rich harvest of contemporary scholarship to present a leading-edge account of ancient China and its antecedents. With handy pedagogical features such as maps and illustrations, as well as an extensive list of recommendations for further reading, Ancient China: A History is an important resource for undergraduate and postgraduate courses on Chinese History, and those studying Chinese Culture and Society more generally." -- Publisher's description